Faktor-faktor yang Mempengaruhi Komuter dan Migrasi Tenaga Kerja Sirkuler di Wilayah GERBANGKERTASUSILA - Devanto Shasta Pratomo; Erlyn Yuniashri; Kukuh Arisetyawan; Brillian Akbar Aminullah; Christiayu Natalia (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study investigates the dynamics of labour migration in the Gerbangkertasusila (Greater Surabaya) region and identifies various factors influencing workers’ decisions to commute, migrate circularly, or permanently. Utilizing data from the 2023 National Labour Force Survey (SAKERNAS) and applying a multinomial logit model, the analysis addresses research gaps related to complex migratory patterns in rapidly urbanizing areas of Indonesia. The result suggested that individuals with higher education levels are significantly more likely to commute than to migrate permanently, while employment in the formal, service, and manufacturing sectors also increases the likelihood of commuting and circular migration. Married individuals are more inclined toward permanent migration, driven by a preference for family stability, whereas urban residents are less likely to engage in circular migration. These findings highlight  the need for targeted urban and labor policies that address mobility preferences based on education, sectoral employment, and household structure to ensure inclusive and balanced regional development. The study suggests that to support inclusive regional development, policymakers should invest in integrated transportation infrastructure, design mobility-support programs for circular migrants, and ensure gender-sensitive commuting systems. These measures will help manage urban growth and enhance equitable access to employment across the region.